G. lamblia and H. pylori infections among mentally challenged individuals in rehabilitation centers in Alexandria, Egypt - Faika I Hassanein; Amany I Shehata; Rashad Abdul-Ghani (Journal of Infection in Developing Countries)
Introduction: Concomitant infections with pathogens are common, particularly when there are shared modes of infection or when one pathogen promotes the other. Residence among closed-type care institutions may pose an additional risk of such infections. Mentally challenged patients in rehabilitation centers constitute one of the special needs groups exposed to parasitic infections, including giardiasis. Several studies reported concomitant infection with G. lamblia and H. pylori worldwide and in Egypt; however, the co-existence of these two pathogens among mentally challenged individuals remains unexplored. The present study aimed to study the prevalence and association between G. lamblia and H. pylori among mentally challenged patients in rehabilitation centers in Alexandria, Egypt.